Prevalence and risk factors for cardiovascular disease among chronic kidney disease patients: results from the Chinese cohort study of chronic kidney disease (C-STRIDE). Issue 1 (December 2017) - Yuan, Jun; Zou, Xin-Rong; Han, Si-Ping; Cheng, Hong; Wang, Lan; Wang, Jin-Wei; Zhang, Lu-Xia; Zhao, Ming-Hui; Wang, Xiao-Qin
Abstract Background Although a high incidence of cardiovascular disease (CVD) is observed among chronic kidney disease (CKD) patients in developed countries, limited information is available about CVD prevalence and risk factors in the Chinese CKD population. The Chinese Cohort of Chronic Kidney Disease (C-STRIDE) was established to investigate the prevalence and risk factors of CVD among Chinese CKD patients. Methods Participants with stage 1–4 CKD (18–74 years of age) were recruited at 39 clinical centers located in 28 cities from 22 provinces of China. At entry, the socio-demographic status, medical history, anthropometric measurements and lifestyle behaviors were documented, and blood and urine samples were collected. Estimated glomerular filtration rate (eGFR) was calculated by the CKD-EPI creatinine equation. CVD diagnosis was based on patient self-report and review of medical records by trained staff. A multivariable logistic regression model was used to estimate the association between risk factors and CVD. Results Three thousand four hundred fifty-nine Chinese patients with pre-stage 5 CKD were enrolled, and 3168 finished all required examinations and were included in the study. In total, 40.8% of the cohort was female, with a mean age of 48.21 ± 13.70 years. The prevalence of CVD was 9.8%, and in 69.1% of the CVD cases cerebrovascular disease was observed. Multivariable analysis showed that increasing age, lower eGFR, presence of hypertension, abdominal aorta calcification and diabetes were associated with comorbid CVD among CKD patients. The odds ratios and 95% confidence intervals for these risk factors were 3.78 (2.55–5.59) for age 45–64 years and 6.07 (3.89–9.47) for age ≥65 years compared with age <45 years; 2.07 (1.28–3.34) for CKD stage 3a, 1.66 (1.00–2.62) for stage 3b, and 2.74 (1.72–4.36) for stage 4 compared with stages 1 and 2; 2.57 (1.50–4.41) for hypertension, 1.82 (1.23–2.70) for abdominal aorta calcification, and 1.70 (1.30–2.23) for diabetes, respectively. Conclusions We reported the CVD prevalence among a CKD patient cohort and found age, hypertension, diabetes, abdominal aorta calcification and lower eGFR were independently associated with higher CVD prevalence. Prospective follow-up and longitudinal evaluations of CVD risk among CKD patients are warranted.